THE CRITICAL SUCCESS FACTORS AND CHALLENGES IN E-PROCUREMENT ADOPTION AMONG LARGE SCALE MANUFACTURING FIRMS IN NAIROBI, KENYA - James Mauti Mose; James Muranga Njihia; Peterson Obara Magutu (European Scientific Journal, ESJ, 2013)
E-Procurement is more than just a system for making purchases online. Some companies implement e-procurement and succeed while others fail. This study was carried out on the adoption of e-procurement among large scale manufacturers in Nairobi, Kenya. The study had three objectives: To ascertain the extent to which large scale manufacturers in Nairobi have adopted e-procurement; to determine the critical success factors influencing the success of e-procurement in large manufacturing firms in Nairobi and to establish the challenges that face e-procurement adoption in large scale manufacturing firms in Nairobi. The research involved a cross-sectional survey of the large manufacturing companies operating in Kenya. The study adopted a descriptive approach in trying to establish the factors that influence the success of e-procurement projects. A sample size of 46 respondents was selected from a list of 455 large manufacturing companies. Data was collected from the respondents through a questionnaire. The collected data was analyzed using SPSS and presented in tables. The study revealed that majority of the large scale manufacturers in Nairobi, Kenya has adopted e-procurement with the following e-procurement practices: online advertisement of tenders, receiving online submission of proposals for the tenders, and short listing suppliers online among others. The five critical success factors identified were: employees and management commitment to success of adoption; reliability of information technology and supplier performance; monitoring the performance of e-procurement systems; ﻿user acceptance of e-procurement systems and top management support. The challenges established are: resistance to change from employees, lack of e-procurement approval by company board, existence of old IT equipment among the firms that need overhaul and lack of managerial support. The study recommends that large scale manufacturers in Nairobi need to incorporate all the e-procurement activities into the system; they need to find out ways of encouraging employees to make use of e-procurement systems as well as find ways of addressing the factors that are critical to the success of e-procurement. This will enable them to improve adoption of e-procurement.